Pengaruh Persepsi Dukungan Sosial Teman Sebaya Terhadap Regulasi Emosi Pada Mahasiswa Perantau di Medan - Della Theresia Manurung; Nenny Ika Putri Simarmata (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study investigates the influence of peer social support on emotion regulation among migrant students in Medan, Indonesia. Migrant students often face a range of adaptation challenges, including adjusting to new social environments, managing academic demands, and dealing with feelings of homesickness. These experiences can lead to increased levels of stress and anxiety, making effective emotion regulation a critical psychological skill. The research adopts an associative quantitative approach and involves a sample of 350 migrant students enrolled in various universities across Medan. The sample was selected based on the Isaac and Michael table with a 5% margin of error. Data were collected using validated scales measuring peer social support and emotion regulation, both employing a Likert-scale format. Statistical analysis was conducted using simple linear regression via SPSS 27.0. The results show that peer social support has a significant positive effect on emotion regulation, as indicated by a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) is 0.113, meaning that peer social support accounts for 11.3% of the variance in emotion regulation, with the remaining 88.7% influenced by other factors. The regression equation Y = 33.595 + 0.253X reflects a direct positive relationship between the two variables. Most participants were categorized as having moderate levels of emotion regulation (82.9%) and high levels of peer social support (54.3%). These findings highlight the vital role of peer social support in enhancing the emotional well-being of migrant students and suggest that fostering strong peer connections can contribute to more effective emotional coping strategies in academic and social contexts